The distorted path to high-growth entreprenurship - Tanesia, Cindy Yoel (Advances in business related scientific research journal, 2025)
This study investigates the relationship between growth opportunity recognition, ambitious proactivity, and high-growth entrepreneurial intention, with high-growth entrepreneurial self-efficacy as a mediating variable. A digital survey of 400 Generation Z individuals who have taken entrepreneurship courses in higher education was analyzed using structural equation modelling (SEM) with AMOS 26. The findings reveal that ambitious proactivity significantly enhances both high-growth entrepreneurial selfefficacy and high-growth entrepreneurial intention. In contrast, growth opportunity recognition exhibits a complex dynamic—while it positively influences high-growth entrepreneurial self-efficacy, its direct effect on highgrowth entrepreneurial intention is negative, indicating that high-growth entrepreneurial self-efficacy functions as a distorter variable. This study highlights the complex interaction of psychological traits and opportunity recognition in shaping entrepreneurial ambition, offering new insights into high-growth entrepreneurship development
Keywords: entrepreneurial intention; entrepreneurial self-efficacy; high-growth entrepreneurship; opportunity recognition